2020
DOI: 10.12691/ajnr-8-5-11
|View full text |Cite
|
Sign up to set email alerts
|

Examining Nurses’ Theoretical Knowledge, Attitude, and Practice of Cardio-pulmonary Resuscitation in Hospitals and Primary Health Care Settings in South Sharqiyah, Sultanate of Oman

Abstract: Objectives: This study attempts to identify the level of knowledge, attitude and practice of CPR among nurses in South Sharqyiah governorate, Oman. Moreover, it evaluates the association between the knowledge score and the selected variables. This will help to review the effectiveness of current CPR training, thus set up recommendations for better CPR programs. Method: This descriptive cross-sectional study was conducted between April and July 2019 in governmental hospitals and Primary Health care (PHC) instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
2
4
1
Order By: Relevance
“…The results of the study indicate a concerning outlook of nurses toward CPR, with the majority displaying negative attitudes toward administering mouth-to-mouth resuscitation in the absence of a mask. These findings align with the conclusions of a study conducted by Abebe et al (2021) but contrasts with other studies that reported positive attitudes among nurses toward CPR (Hendy et al, 2023; Nasri & Bulushi, 2020). Negative attitudes toward emergency situations can be attributed to factors such as confusion, panic, lack of education, and fear of contracting infections (Hendy et al, 2023).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of the study indicate a concerning outlook of nurses toward CPR, with the majority displaying negative attitudes toward administering mouth-to-mouth resuscitation in the absence of a mask. These findings align with the conclusions of a study conducted by Abebe et al (2021) but contrasts with other studies that reported positive attitudes among nurses toward CPR (Hendy et al, 2023; Nasri & Bulushi, 2020). Negative attitudes toward emergency situations can be attributed to factors such as confusion, panic, lack of education, and fear of contracting infections (Hendy et al, 2023).…”
Section: Discussionsupporting
confidence: 82%
“…The survey utilized nine yes/no questions (α = 0.71) for this section. The participants engaged in introspection and shared the self-reported CPR techniques they utilized during their most recent emergency by answering declarative statements regarding their opinions of their practice, e.g., “I wore latex gloves before commencing CPR,” “I pinched the patient's nostril before giving mouth-to-mouth ventilation,” and “I checked for the patient's pulse rate before commencing CPR.” Numerous studies have employed declarative statements to assess the practice of nurses (Abebe et al, 2021; Guteta, 2022; Nasri & Bulushi, 2020). The overall score spanned between a minimum of 9 and a maximum of 18, with a score of 14 to18 denoting good practice, while scores of 9 to 13 indicated poor practice.…”
Section: Methodsmentioning
confidence: 99%
“…Other contradictory finding was reported by Khatun et al, 32 where among all respondents 70.62% had neutral, 15% positive, and 14.38% negative attitudes about performing CPR. Furthermore, Nasri and Bulushi 4 reported that higher positive attitudes were found slightly more frequently among nurses with a diploma (63.2%) than a bachelor’s and above (46.4%) and that nurses who worked in public health-care institutions were found to have more positive attitudes (87.8%) than hospital nurses (43.8%). This study found a significant association between attitudes and validation of BLS certificate ( P <0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses require the right knowledge and abilities to conduct safe and successful resuscitation. 4 All health-care personnel are required to be proficient in CPR, which is considered a core emergency skill. In underdeveloped nations versus developed nations, CPR is still a relatively recent practice.…”
Section: Introductionmentioning
confidence: 99%
“…As a component of nurses' behavioural competence, our study participants acknowledged the role of adequate knowledge and skills acquisition in the quality of resuscitation. Interestingly so, varying levels of nurses' knowledge of resuscitation have been reported by several scholars [21,[48][49][50], implying that not all nurses have adequate knowledge and skills required for performing resuscitation. Sometimes, having adequate knowledge about resuscitation is not the single most important measure of the level of competence when it comes to resuscitation.…”
Section: "…The Way They Respond To the Command To Do Resuscitation In...mentioning
confidence: 99%